NILAI INDEKS VEGETASI PENGGUNAAN LAHAN DI KAWASAN HUTAN LINDUNG DESA SEJOLI KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG - Gandari, Didin; Akhbar, Akhbar; Arianingsih, ida (Universitas Tadulako)
This study aims to determine the value of land use / cover vegetation index in the protected forest area of Sejoli Village, Moutong District, Parigi Moutong Regency using the latest landsat 8 recording images in 2015. The study was conducted for three months from November to January 2016, located in the Sejoli Village Protection Forest in Moutong District, Parigi Moutong Regency. The method used in this study is the Landsat image classification technique, which classifies land use / cover to analyze the vegetation index value of land use / cover in protected forests using Landsat imagery 8 latest recording in 2015. Landsat data is processed with AcrGIS version 10 software with several stages include: correction of Geometric and Radiometric, interpretation and image classification (supervised classification), and NDVI analysis (Normalized Differenced Vegetation Index) to determine the level of vegetation density. NDVI analysis results show the digital value of the class of vegetation density is very dense with a range of 0.43 - 0.60 with an area of 1549.59 ha or 81.87% in the class of land use namely primary forest and secondary forest, medium vegetation density with a range of 0.33 - 0.42 with an area of 328.73 ha or 17.37% in the land use class namely plantation and shrub, sparse vegetation density with a range of -0.11 - 0.32 with an area of 14.38 ha or 0.76% in the land use class, namely water, settlements and open land.Keywords: Protection Forest, Vegetation Index, NDVI, Landsat.